2014
DOI: 10.1111/pme.12505
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Therapeutic Patient Education for Adults with Migraine. A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: This systematic review revealed strong-moderate evidence for intermediate-term effectiveness of therapeutic patient education for migraine. Further high-quality RCTs are required for conclusive determination of its effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 79 publications
(210 reference statements)
4
46
0
5
Order By: Relevance
“…There was also a significant improvement in medication use, with 36% of participants reporting a reduction, from prophylactic to symptomatic therapy or no therapy, or from symptomatic therapy to no therapy. These results are essentially consistent with those reported by Kindelan-Calvo et al [16] in their review. Wallasch et al [26], evaluating a multidisciplinary intervention specific for headache, reported also better results: an attacks frequency reduction of 62.7%, a disability degree reduction of 47.4 and an analgesic use reduction of 74.5%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There was also a significant improvement in medication use, with 36% of participants reporting a reduction, from prophylactic to symptomatic therapy or no therapy, or from symptomatic therapy to no therapy. These results are essentially consistent with those reported by Kindelan-Calvo et al [16] in their review. Wallasch et al [26], evaluating a multidisciplinary intervention specific for headache, reported also better results: an attacks frequency reduction of 62.7%, a disability degree reduction of 47.4 and an analgesic use reduction of 74.5%.…”
Section: Discussionsupporting
confidence: 93%
“…The best approach to deal with headache, as well as with other kind of chronic pain where it does exist an important interplay of biological and psychological factors seems to be a combination of pharmacological and non-pharmacological treatments [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous systematic review and meta-analysis, which included 14 studies of patient education interventions in primary care, found that patient education, especially issued by physicians, increases long-term reassurance in patients with acute low back pain 32. Another systematic review and meta-analysis with nine trials reported that therapeutic patient education has an effect for patients with migraine 33. However, one study showed that pain management training of health care professionals is not adequate 34.…”
Section: Discussionmentioning
confidence: 99%
“…Canadian guidelines on acute and prophylactic treatments for migraine have been published, helping clinicians to choose their prescriptions, but pharmacological treatments are not enough . Patient education is one of the keys of chronic disease management, including migraine . Insufficient education may lead to poor compliance and disappointing outcomes.…”
mentioning
confidence: 99%